2016
DOI: 10.1016/j.diabres.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reducing blood pressure on cardiovascular outcomes and mortality in patients with type 2 diabetes: Focus on SGLT2 inhibitors and EMPA-REG OUTCOME

Abstract: Please cite this article as: A.J. Scheen, Effects of reducing blood pressure on cardiovascular outcomes and mortality in patients with type 2 diabetes: focus on SGLT2 inhibitors and EMPA-REG OUTCOME, Diabetes Research and Clinical Practice (2016), doi: http://dx.doi.org/10.1016/j.diabres. 2016.09.016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyeditin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 78 publications
1
24
0
4
Order By: Relevance
“…One marked difference between LEADER and EMPA-REG OUTCOME is the distinctive outcome of a 35% (P < 0.001) reduction in hospitalizations for HF reported with empagliflozin, whereas only a slight, non-significant reduction was noted with liraglutide (-13%, P = 0.14; Table 4). Both liraglutide and empagliflozin reduce systolic blood pressure, an independent risk factor of HF, but the insignificant difference vs the placebo arm in T2D patients with blood pressure already well controlled at baseline cannot explain the marked reduction in hospitalizations for HF in the EMPA-REG OUTCOME [52].…”
Section: Lessons From Leadermentioning
confidence: 97%
“…One marked difference between LEADER and EMPA-REG OUTCOME is the distinctive outcome of a 35% (P < 0.001) reduction in hospitalizations for HF reported with empagliflozin, whereas only a slight, non-significant reduction was noted with liraglutide (-13%, P = 0.14; Table 4). Both liraglutide and empagliflozin reduce systolic blood pressure, an independent risk factor of HF, but the insignificant difference vs the placebo arm in T2D patients with blood pressure already well controlled at baseline cannot explain the marked reduction in hospitalizations for HF in the EMPA-REG OUTCOME [52].…”
Section: Lessons From Leadermentioning
confidence: 97%
“…[68,69]. It is unlikely, however, that they could be explained either by the modest reduction in glycated haemoglobin (HbA1c, though equipoise glucose control in both arms was not achieved), or by the slight reduction in arterial blood pressure in already wellcontrolled T2D patients, [70] or by a common diuretic effect. [71] Even a combination of all these mechanisms appears insufficient to explain the drastic reduction in mortality so that other hemodynamic [67] or metabolic [72] mechanistic alternatives have been proposed, which are not mutually exclusive but still remain to be confirmed.…”
Section: Empa-reg Outcome Trialmentioning
confidence: 98%
“…SGLT-2 inhibitors improve glycemic control, reduce body weight and blood pressure, and are associated with a low risk of hypoglycemia [68]. In clinical trials, an SGLT2 inhibitor (empagliflozin) was found to have a profound effect in reducing cardiovascular and all-cause mortality in patients with T2DM and antecedents of cardiovascular disease [67]. This effect, however, was attributed mostly to a hemodynamic rather than a metabolic effect in part due to osmotic/diuretic effect of the SGLT2 and to the reduction in arterial blood pressure.…”
Section: Kidneysmentioning
confidence: 99%
“…In T2DM subjects, all of the filtered glucose in excess of the Tm is excreted in the urine [64][65][66]. Because sodium and glucose are cotransported in renal proximal tubular cells, T2DM subjects have an increase in total body sodium content and a high risk of hypertension [67]. Inhibition of SGLT-2, which is responsible for approximately 90% of renal glucose reabsorption, increases urinary glucose excretion and lowers blood glucose concentrations.…”
Section: Kidneysmentioning
confidence: 99%